Students emotions evaluation on virtual learning environments - Aballay, Laura Nidia (2022)
The student interacts with the platform Virtual Learning Environment to follow the course lessons. This interaction has a great impact on the student’s learning outcome. The need to design and provide educational platforms and resources that are not only accessible but also attractive to students has been emphasized. Therefore, it is important that users/students have satisfaction with its environment and interface. This article leave a list of emotions to evaluate the functionalities of educational platforms, validated by students and experts. This list of emotions in Spanish will be very useful for the field of Affectivity and Educational Technology, since it has the support of recognized professionals as well as students of higher education, of different ages and countries of origin, which enriches the validity and heterogeneity of the study.